2018
DOI: 10.1002/ece3.4040
|View full text |Cite
|
Sign up to set email alerts
|

Gut microflora may facilitate adaptation to anthropic habitat: A comparative study in Rattus

Abstract: Anthropophilic species (“commensal” species) that are completely dependent upon anthropic habitats experience different selective pressures particularly in terms of food than their noncommensal counterparts. Using a next‐generation sequencing approach, we characterized and compared the gut microflora community of 53 commensal Rattus rattus and 59 noncommensal Rattus satarae captured in 10 locations in the Western Ghats, India. We observed that, while species identity was important in characterizing the microfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
2
3
0
Order By: Relevance
“…R. norvegicus and M. musculus , family Muridae). Varudkar & Ramakrishnan (2018) previously reported a similar pattern while comparing the GM of two phylogenetically related rats in rural and urban habitats. Habitat emerged as the main predictor of GM diversity and composition.…”
Section: Discussionsupporting
confidence: 60%
“…R. norvegicus and M. musculus , family Muridae). Varudkar & Ramakrishnan (2018) previously reported a similar pattern while comparing the GM of two phylogenetically related rats in rural and urban habitats. Habitat emerged as the main predictor of GM diversity and composition.…”
Section: Discussionsupporting
confidence: 60%
“…Specifically, we observed that the structure of gut microbiota differed between categories, but were similar within each category, whatever the phylogenetic distance between small mammal species. Varudkar & Ramakrishnan [ 102 ] previously reported a similar pattern while comparing the GM of two phylogenetically related rats in rural and urban habitats. Habitat emerged as the main predictor of GM diversity and composition.…”
Section: Discussionsupporting
confidence: 56%
“…Diet also strongly influences the gut microbiome. Gut microbes can influence food intake ( Jia et al, 2021 ; Ousey et al, 2023 ), behavior ( Jia et al, 2021 ; Ousey et al, 2023 ) and health ( Fontana and Partridge, 2015 ): in rats, for example, gut microbiota may enhance survival in human-dominated environments, with city-dwelling common black rats containing microflora different from those in non-commensal forest-dwelling species ( Varudkar and Ramakrishnan, 2018 ). It is difficult to causally link microbiome composition to behavior, but there has been some success in invertebrate models ( Petersen and Osvatic, 2018 ).…”
Section: The 10 Questionsmentioning
confidence: 99%